2020
DOI: 10.3892/etm.2020.9504
|View full text |Cite
|
Sign up to set email alerts
|

Icariin enhances cell survival in lipopolysaccharide‑induced synoviocytes by suppressing ferroptosis via the Xc‑/GPX4 axis

Abstract: The mechanism of action of synovitis, as the vital pathological process of rheumatoid arthritis and osteoarthritis, remains to be elucidated. The effects and the mechanism of icariin (ICA), which is a promising therapeutic agent in synovitis, was investigated in the present study. In addition, ferroptosis, a vital cell process involved in several diseases, was also studied in synovitis for the first time. Lipopolysacc haride (LPS)-induced synoviocytes served as a synovitis cell model. The cells were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 55 publications
3
71
0
Order By: Relevance
“…These results suggested that ICA protects H/R‐induced cardiomyocytes by inhibiting ferroptosis. Consistently, ICA prevents lipopolysaccharide‐induced cell death in synoviocytes by suppressing ferroptosis [ 44 ].…”
Section: Discussionmentioning
confidence: 88%
“…These results suggested that ICA protects H/R‐induced cardiomyocytes by inhibiting ferroptosis. Consistently, ICA prevents lipopolysaccharide‐induced cell death in synoviocytes by suppressing ferroptosis [ 44 ].…”
Section: Discussionmentioning
confidence: 88%
“…Owing to that plant‐derived phenolics have been consumed by human beings for thousands of years and proven to play a safe and beneficial role, phenolics are thus postulated to be a library of safe ferroptosis inhibitors. In fact, some plant‐derived phenolic flavonoids have been indicated as natural ferroptosis‐inhibitors, such as galangin, [5] icariin, [6] and baicalein [7] . Recently, our team also found that quercetin and its Diels‐Alder anti ‐dimer could also act as ferroptosis‐inhibitors [8] .…”
Section: Figurementioning
confidence: 93%
“…Early studies have confirmed that glutathione peroxidase (GPX) activity in polymorphonuclear leucocytes of RA patients with high persistent disease activity is reduced (16). Luo et al (17) found that RSL3, a ferroptosis activator, can induce ferroptosis in synovial cells and aggravate synovitis. Transferrin receptor 1 (TFR1) and nuclear receptor coactivator 4 (NCOA4) were upregulated, but system Xc-(an amino acid transporter mediating the exchange of extracellular cystine and intracellular glutamate) and GSH-glutathione peroxidase 4 (GPX4), as well as nuclear factor erythroid 2-related factor 2 (Nrf2, a transcriptional factor that induces antioxidative and cytoprotective responses), were downregulated by RSL3 treatment.…”
Section: Introductionmentioning
confidence: 98%